Monolithic integration of enhancement/depletion-mode high electron mobility transistors using hydrogen plasma treatment. (12th February 2019) - Hao, Ronghui; Sun, Chi; Fang, Bin; Xu, Ning; Tao, Zhifu; Zhang, Hui; Wei, Xing; Lin, Wenkui; Zhang, Xiaodong; Yu, Guohao; Zeng, Zhongming; Cai, Yong; et al.
Abstract: We demonstrate a planar technique of hydrogen plasma treatment for monolithic integration of enhancement/depletion (E/D)-mode GaN high electron mobility transistors (HEMTs). By hole compensation mechanism, E-mode and D-mode HEMTs based on p-GaN/AlGaN/GaN heterojunctions are simultaneously realized on the same wafer. The fabricated direct-coupled FET logic inverter with a driver/load ratio of 10 exhibits a large output logic swing of 4.78 V, wide noise margins, an ultralow threshold hysteresis of 13 mV, and good temperature stability up to 300 °C, while the fabricated 11-stage ring oscillator shows a propagation delay of 0.8 ns/stage at V DD  = 5 V.